Pelaksanaan Akad Pembiayaan Murabahah Pada Perbankan Syariah yang Terdaftar di Bursa Efek Indonesia - Waruwu, Noviza Asni (Journal Research of Economic and Bussiness, 2023)
The aim of this research is to analyze the recognition and measurement, presentation and disclosure of murabahah financing transactions based on PSAK 102 murabahah financing at PT. Bank BTPN Syariah Tbk. The research approach used is a qualitative approach with descriptive methods. The research location taken by the author was at PT. Bank BTPN Syariah Tbk. The data used by researchers is secondary data, which collects data through documentation and literature. This research compares the results of the annual report published by PT. Bank BTPN Syariah Tbk with PSAK 102 concerning murabahah financing. The research results show that the recognition and measurement of murabahah income at PT. Bank BTPN Syariah Tbk, murabahah financing consists of recording acquired assets, recognition and measurement of murabahah profits that are not in accordance with the implementation of PSAK 102, and recognition and measurement of receivables regarding murabahah accounting in practice for murabahah financing carried out by PT. Bank BTPN Syariah is in accordance with PSAK 102 concerning murabahah accounting as a guideline.